Thermoelectric transport properties of pristine and Na-doped SnSe1−xTex polycrystals. Issue 44 (26th October 2015) - Wei, Tian-Ran; Wu, Chao-Feng; Zhang, Xiaozhi; Tan, Qing; Sun, Li; Pan, Yu; Li, Jing-Feng
Abstract : Pristine and Na-doped SnSe1− x Te x solid solutions exhibit reduced thermal conductivities yielding ZT max = 0.72 with energy barrier scattering in the carrier transport. Abstract : SnSe, a "simple" and "old" binary compound composed of earth-abundant elements, has been reported to exhibit a high thermoelectric performance in single crystals, which stimulated recent interest in its polycrystalline counterparts. This work investigated the electrical and thermal transport properties of pristine and Na-doped SnSe1− x Te x polycrystals prepared by mechanical alloying and spark plasma sintering. It is revealed that SnSe1− x Te x solid solutions are formed when x ranges from 0 to 0.2. An energy barrier scattering mechanism is suitable for understanding the electrical conducting behaviour observed in the present SnSe polycrystalline materials, which may be associated with abundant defects at grain boundaries. The thermal conductivity was greatly reduced upon Te substitution due to alloy scattering of phonons as well explained by the Debye model. Due to the increased carrier concentration by Na-doping, thermoelectric figure of merit ( ZT ) was enhanced in the whole temperature range with a maximum value of 0.72 obtained at a relatively low temperature (773 K) for Sn0.99 Na0.01 Se0.84 Te0.16 .